Pengaruh Waktu Perendaman Terhadap Uji Kuat Tekan Paving Block Menggunakan Campuran Tanah dan Semen dengan Alat Pemadat Modifikasi - Prestika, Mutiara; Adha, Idharmahadi; Setyanto, Setyanto (Universitas Lampung, 2016)
Paving Block is the product of a cement building materials that are used as an alternative groundcover of surface hardening. In general, paving block itself is usually made from a mixture ofcoarse aggregate (gravel) and fine aggregate (sand) with a mixture of cement and water areformed according to demand. So in this study, will provide another alternative to using a mixtureof soil and cement as well as soaking to know the effect of compressive strength.Soil samples were taken from Kota Baru, South Lampung. The mixture used is 20% cement and80% is soil, with a variation of immersion 7, 14, 21, and 28 days. Soaking were conducted withand without the combustion process to be seen compressive strength and water absorption.The result is that the compressive strength without burning has increased up to -28 immersion dayby 38.8%, while the compressive strength is experiencing burning decreased to 28 days amountedto 20.63%.Despite an increase in the sample without fuel, and a decrease in samples that undergocombustion, which produced the same compressive strength together to meet quality specificationD on SNI 03-0691-1996. Value of water absorption of pre-combustion meets the specification SNI03-0691-1996 which is 3%-10%. While with combustion does not meet due to exceed 10 %.Keys : paving block, cement, compressive strength,water absorption